Specimens and culture media for the laboratory diagnosis of typhoid fever. - Wain, J; Diep, T; Bay, P; Walsh, A; Vinh, H; Duong, N; Ho, V; Hien, T; Farrar, J; White, N; Parry, C; Day, N (2008)
BACKGROUND: Culture of S. Typhi is necessary for the definitive diagnosis of typhoid fever and provides isolates for antibiotic susceptibility testing and epidemiological studies. However, current methods are not fully optimised and sourcing culture media and bottles for culture media may be problematic. METHODOLOGY: In two hospital laboratories in Viet Nam, comparisons of media for blood and stool culture were conducted. The effect of the volume of blood or stool on culture positivity rate was examined and direct plating of the blood buffy coat was trialed. RESULTS: For 148 suspected typhoid fever cases, ox bile broth (58 positive) and brain-heart infusion broth containing saponin (63 positive), performed equally well. For 69 confirmed adult typhoid fever cases, large-volume (15 ml) blood culture gave the same sensitivity as 1 ml of bone marrow culture. For 44 confirmed typhoid fever cases, the direct plating of the buffy coat was positive in 28 cases. For 263 positive stool cultures, selenite F and selenite mannitol performed equally well and culturing 2 g rather than 1g increased the isolation rate by 10.5%. CONCLUSIONS: For the diagnosis of typhoid fever by blood culture the medium should be a rich nutrient broth containing a lysing agent. In adults 1 ml bone marrow or 15 ml blood culture gave similar results. Where isolates are needed for susceptibility testing or epidemiological studies, but resources for culture are scarce, direct plating of the blood buffy coat can be used with a 50% fall in sensitivity compared to standard blood culture.